TREATMENT OF HERPES ASSOCIATED ERYTHEMA MULTIFORME (HAEM): TATALAKSANA HERPES ASSOCIATED ERYTHEMA MULTIFORME (HAEM) - Raziv Ganesha; Rina Kartika Sari (Interdental Jurnal Kedokteran Gigi (IJKG), 2023)
Introduction: Herpes Associated Erythema Multiforme (HAEM) is Erythema multiforme (EM) caused herpes virus infection.  EM a caused by an acute hypersensitivity reaction that occurs in the mucocutaneous area. HAEM is hypersensitivity reaction that occurs due to a hypersensitivity reaction to the herpes virus. Case: 17 year old male complaints of itching and dry on his lips since 5 days ago. patient said that ± 7 days ago he had a fever which lasted for 2 days then after the fever went down his lips felt itchy and dry. On clinical examination, desquamation with yellowish brown crusts was found on the vermilion of the upper and lower lips. Case Treatment: patient is given Aloclair® Gel and Becomzet®. Patient is referred for a complete blood count, Total IgE and IgM and IgG HSV-1 antibody testing. The patient was then given hydrocortisone cream 2.5% used 3 times a day. The patient recovered 10 days after the first visit. Discussion: HAEM is triggered by an immunological response in which an immune complex reaction occurs as a result of an immune response to certain antigens such as the herpes simplex virus or certain types of drugs. In cases of HAEM the herpes virus that triggers it is usually HSV-1 & HSV-2. Diagnosis is confirmed by Total IgE and HSV-1 Antibody Tests. Conclucion: Management of cases of HAEM can be successfully determined by establishing the correct diagnosis which requires investigations so that we can rule out the differential diagnosis and provide appropriate treatment